The effects of weight categories on the time-motion analysis of female high-level judo athletes between the 2016 and 2020 Olympic cycles - Barreto, Lindsei Brabec Mota; Miarka, Bianca; dos Santos Silva, Roberto Jerônimo; Bragazzi, Nicola Luigi; Slimani, Maamer; Znazen, Hela; Soto, Dani Alexis Sorbazo; Aedo-Muñoz, Esteban Ariel; Brito, Ciro Jose (Frontiers in Psychology, 2022)
This study compared the time of female judo combat phases in international competitions between two Olympic cycles (2016; 2020) according to weight divisions (48 kg = 132; 52 kg = 72; 57 kg = 109; 63 kg = 96; 70 kg = 69; 78 kg = 106; >78 kg = 82; total = 666 combats/cycle). The behaviors of 1,332 high-level female judo combats were randomly observed over two Olympic cycles (2016 = 666; 2020 = 666) from the top 20 athletes in the world ranking by weight division. We performed time-motion analysis according to the combat phase and sequential judo actions (approach, gripping, attack, defense, groundwork, pause, and effort: pause ratio) considering the moment when the combat ended (Regular time = RT; Golden score = GS). The weight division groups were compared between Olympic cycles (2016; 2020), and p < 0.05 was defined as significant. The main results showed that 2020 athletes spent less time in the gripping (p = 0.005), attack (p < 0.001), defense (p < 0.001), groundwork (p<0.001) and pause (p = 0.002) phases than 2016 athletes. However, compared by the end-of-combat, 2020 female athletes spent less time in all combat phases for RT combats (p < 0.001), and more time in the approach phase for GS combats (p < 0.05) than in 2016. The 2016 weight divisions showed a higher diversity in the effort: pause ratio (2.5:1–3.4:1), whereas the 2020 weight divisions had values closer to each other (2.8,1–3:1). Analyzing each weight division separately and by the end-of-combat, the main results showed that (p < 0.05): 48, 63, 70, and 78 kg reduced the time in almost every phase of RT combat (except for: 63 kg = gripping and attack; 70 kg = approach and groundwork; 78 kg = approach); 48 and 57 kg increased the groundwork time in GS combats whereas 78 kg decreased; 52 kg and 78 kg increased the GS approach time. The temporal behavior of the combats changed between the Olympic cycles with different rules. These data must be considered to understand the characteristics of each group and to prescribe specialized training in female judo.